ANALISIS RATIO KEUANGAN UNTUK MENINGKATKAN KINERJA PERUSAHAAN PADA KOPERASI KARYAWAN PEDAMI KOTA BANJARMASIN - Ilham Ilham; Erni Alfisah; Murhanawaty Syamsi (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2016)
Cooperative employees Pedami Banjarmasin has the task of coordinating andimplementing the management, provision, exploitation and pemasran cooperativeefforts in accordance with the direction, objectives and business strategy. KopkarPedami Banjarmasin is Banjarmasin PDAM employee-owned cooperative that aims toprosper and provide services to its members.The purpose of this study was to determine the financial performance KopkarPedami Banjarmasin by the Minister of Cooperatives and Small and Medium Enterprisesof the Republic of Indonesia 14 / Per / M.KUKM / XII / 2009. The data used in thisresearch is secondary data and the data collected through observation, interviews anddocumentation. Assessment of financial performance Kopkar Pedami Banjarmasin basedon financial statements (balance sheet and income statement) in 2010-2013 from theaspect of productivity in accordance with the Decree of the Minister of Cooperatives andSmall and Medium Enterprises of the Republic of Indonesia 14 / Per / M.KUKM / XII /2009. On guidelines for assessment of cooperative achievement.Based on the research that results soundness Kopkar Pedami Banjarmasin seenfrom the aspect of productivity is 2010 result by 53, 125 means health Kopkar PedamiBanjarmasin categorized C (Good), in 2011 the results of 68, 75 means health KopkarPedami Banjarmasin categorized B (Good) in 2012 result by 56, 25 means that the healthof the city of Banjarmasin categorized Kopkar Pedami C (Good) in 2013 result by 59, 375means that the health of the city of Banjarmasin categorized Kopkar Pedami C (Good)